FACTORS IDENTIFICATION AFFECTING OCCUPATIONAL HEALTH AND SAFETY SYSTEM USING DELPHI METHOD AT INDONESIA REPRESENTATIVE COUNCIL BUILDING - Wibowo, Prasetyo Hari; Waty, Mega (Jurnal Infrastruktur, 2024)
Negligence in carrying out renovation work by the contractor, namely incidents or events at the DPR RI Building, this can disrupt the productivity and continuity of legislative activities. Implementation of OHSMS is a preventive action for incidents that could result in fatality in the workplace. The impact is the postponement of important agendas. This research aims to analyze the factors that influence the OHSMS in the DPR RI Building. Qualitative approach is used with questionnaires, in-depth interviews and document analysis as data collection methods. The results identified a number of key factors that influence the implementation of the OHSMS in the DPR RI Building. These factors are interrelated and contribute to creating a safe and healthy work environment in the DPR RI Building. The results of this research have important implications in improving OHS in the DPR RI Building and may be applied in similar organizational contexts.